An organic modified montmorillonite clay reinforced arnosulfide insulation paper and a preparation method thereof
Patent Information
- Application Number
- CN202611213997.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]针对现有技术中存在的问题,本发明提供一种有机改性蒙脱土增强的芳砜纶绝缘纸及其制备方法,解决了直接利用钠基蒙脱土与芳砜纶纤维复合时出现的绝缘纸孔隙结构不均匀、吸湿率较高、局部电场畸变和击穿强度下降问题
本发明一种有机改性蒙脱土增强的芳砜纶绝缘纸的制备方法,通过采用十八烷基三甲基溴化铵(OTAB)对钠基蒙脱土进行有机插层改性,提高蒙脱土层间距及表面有机化程度,提高了蒙脱土在芳砜纶纤维浆料中的分散性及界面相容性,使其能够在芳砜纶纤维网络中实现均匀分散,并与芳砜纶纤维形成稳定的界面结合;同时利用高分散层状蒙脱土对纤维间孔隙进行填充和细化,构建曲折的电荷迁移路径,降低局部电场集中和界面极化,从而实现芳砜纶绝缘纸绝缘性能、耐湿性能及环境稳定性的协同提升。本发明显著提高了芳砜纶绝缘纸的交流击穿强度、绝缘性能,降低了绝缘纸的吸湿性能(吸湿率),提高了环境稳定性,具有良好的耐热性能和工程应用价值,可满足高性能纸基绝缘材料的应用需求。
Smart Images

Figure CN122918893A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of special paper and electrical insulation materials, specifically an organically modified montmorillonite-reinforced aramid insulating paper and its preparation method. Background Technology
[0002] Polysulfonamide (PSA) is a high-performance fiber material with excellent heat resistance, flame retardancy, mechanical properties, and electrical insulation. PSA insulating paper, made from PSA, combines good heat resistance, dimensional stability, and electrical insulation properties, and is widely used in electrical insulation fields such as high-voltage motors, dry-type transformers, and rail transportation. With the development of power equipment towards higher voltage, larger capacity, and higher power density, higher requirements are placed on the insulation performance and service reliability of PSA insulating paper.
[0003] Existing aramid fiber insulating paper mainly relies on fiber interlacing to form the paper sheet structure. Due to the high surface polarity of aramid fibers and the presence of a certain number of pores within the paper sheet, it easily absorbs moisture and generates interfacial polarization, leading to a decrease in dielectric properties and local electric field distortion. This, in turn, affects the breakdown strength and long-term operational stability of the insulating paper. Therefore, improving the pore structure of the paper sheet, reducing hygroscopicity, and enhancing insulation performance have become important directions for the improvement of aramid fiber insulating paper.
[0004] Sodium-based montmorillonite (Na-MMT) is widely used in the modification of polymer composites due to its excellent insulation properties, large specific surface area, and layered structure. However, unmodified sodium-based montmorillonite is highly hydrophilic and prone to agglomeration in fiber slurries. It also exhibits poor interfacial compatibility with aramid fibers, making it difficult to disperse uniformly within the paper sheet. This not only limits its reinforcing effect but may also introduce new interfacial defects, resulting in uneven pore structure, high moisture absorption, local electric field distortion, and decreased breakdown strength in the insulating paper. Summary of the Invention
[0005] To address the problems existing in the prior art, this invention provides an organically modified montmorillonite-reinforced aramid fiber insulating paper and its preparation method, which solves the problems of uneven pore structure, high moisture absorption, local electric field distortion and decreased breakdown strength that occur when sodium-based montmorillonite is directly combined with aramid fiber.
[0006] This invention is achieved through the following technical solution: A method for preparing organically modified montmorillonite-reinforced arylsulfone insulating paper specifically includes the following steps: Step 1: Mix the octadecyltrimethylammonium bromide-modified sodium montmorillonite dispersion with aramid slurry until homogeneous. The mass of the octadecyltrimethylammonium bromide-modified sodium montmorillonite is 6-12% of the aramid slurry to obtain a composite slurry. Step 2: The composite pulp is formed into paper sheets using a wet papermaking process, and then filtered, dehydrated and dried in sequence to obtain the preliminary composite insulating paper. Step 3: The preliminarily formed composite insulating paper is hot-pressed at 220-300 ℃ to obtain organically modified montmorillonite-reinforced aramid insulating paper.
[0007] A further improvement of the present invention is that: The sodium montmorillonite dispersion described in step 1 is obtained as follows: an aqueous suspension of sodium montmorillonite is reacted with an aqueous solution of octadecyltrimethylammonium bromide at 60–90 °C for 2–5 h. The amount of octadecyltrimethylammonium bromide added is 1–1.5 times the cation exchange capacity of sodium montmorillonite. The product is then filtered, washed, dried, and dispersed in an aqueous ethanol solution at a ratio of 1 g: 100 mL to obtain the sodium montmorillonite dispersion.
[0008] In the aqueous suspension of sodium montmorillonite, the ratio of sodium montmorillonite to deionized water is 1 g:(10-30) mL, the volume of the aqueous suspension of sodium montmorillonite is the same as that of the aqueous solution of octadecyltrimethylammonium bromide, and in the aqueous ethanol solution, the volume ratio of ethanol to deionized water is (1-4):(1-4).
[0009] The pH value of the aqueous solution of octadecyltrimethylammonium bromide is 2 to 3.
[0010] The aramid slurry described in step 1 is obtained by the following process: aramid short-cut fibers and aramid precipitated fibers are added to deionized water at a mass ratio of (3-7):(3-7) and dispersed evenly to obtain the aramid slurry.
[0011] In the aramid slurry, the total mass of aramid chopped fibers and aramid precipitated fibers is 0.1% to 1% of the mass of the aramid slurry.
[0012] Step 1: Stir the sodium montmorillonite dispersion modified with octadecyltrimethylammonium bromide and aramid slurry at 300-800 r / min for 5-10 min to obtain a composite slurry.
[0013] The drying process described in step 2 is carried out at 80–120 °C to obtain a pre-formed composite insulating paper with a basis weight of 60–120 g / m².
[0014] The composite insulating paper initially formed in step 3 is hot-pressed at 220–300 °C and 8–15 MPa for 5–20 min.
[0015] An organically modified montmorillonite-reinforced aramid insulating paper obtained by the preparation method of organically modified montmorillonite-reinforced aramid insulating paper according to any one of the above methods.
[0016] Compared with the prior art, the present invention has the following beneficial technical effects: This invention discloses a method for preparing organically modified montmorillonite-reinforced aramid fiber insulating paper. The method involves organically intercalating sodium-based montmorillonite with octadecyltrimethylammonium bromide (OTAB) to improve the interlayer spacing and surface organication of the montmorillonite. This enhances the dispersibility and interfacial compatibility of montmorillonite in the aramid fiber slurry, enabling it to achieve uniform dispersion within the aramid fiber network and form a stable interfacial bond with the fibers. Simultaneously, the highly dispersed layered montmorillonite fills and refines the pores between fibers, constructing a tortuous charge migration path, reducing local electric field concentration and interfacial polarization. This results in a synergistic improvement in the insulation performance, moisture resistance, and environmental stability of the aramid fiber insulating paper. This invention significantly improves the AC breakdown strength and insulation performance of the aramid fiber insulating paper, reduces its moisture absorption (hygroscopicity), enhances environmental stability, and exhibits good heat resistance and engineering application value, meeting the application requirements of high-performance paper-based insulating materials. Attached Figure Description
[0017] Figure 1 This is a schematic diagram of the process flow of the preparation method described in this invention.
[0018] Figure 2a This is a physical image of the sample from Embodiment 1 of the present invention.
[0019] Figure 2b To be Figure 2a A picture of the sample after it has been bent.
[0020] Figure 2c To be Figure 2a A picture of the sample after it has been folded.
[0021] Figure 3 The image shows a comparison of the SEM morphology and water contact angle of Na-MMT and OTAB-MMT obtained in Example 1.
[0022] Figure 4a The XRD patterns of Na-MMT and OTAB-MMT obtained in Example 1 of this invention are shown.
[0023] Figure 4b The images show the FTIR spectra of Na-MMT and OTAB-MMT obtained in Example 1 of this invention.
[0024] Figure 5 This is a comparison chart showing the effect of different Na-MMT and OTAB-MMT contents on the breakdown strength of composite PSA insulating paper according to the present invention.
[0025] Figure 6The pore size distribution comparison curves are for PSA paper, 8% Na-MMT / PSA paper, and 8% OTAB-MMT / PSA paper obtained in Example 1 of this invention.
[0026] Figure 7 This invention provides a comparison of the saturated moisture absorption rates of different OTAB-MMT contents. Detailed Implementation
[0027] The present invention will be further described in detail below with reference to specific embodiments. These descriptions are for explanation purposes only and are not intended to limit the scope of the invention.
[0028] This invention discloses a method for preparing organically modified montmorillonite-reinforced arylsulfone insulating paper, such as... Figure 1 As shown, the specific steps include the following: Step 1, Preparation of Organically Modified Montmorillonite Sodium-based montmorillonite (Na-MMT) was added to deionized water at a mass-to-volume ratio of 1 g:(10-30) mL. The mixture was stirred at 300-600 r / min for 1-5 h at 60-90 °C to fully disperse the montmorillonite and prepare a suspension.
[0029] Octadecyltrimethylammonium bromide (OTAB) was dissolved in an equal volume of deionized water. The amount of OTAB added was 1–1.5 times the cation exchange capacity (CEC) of montmorillonite, and the pH of the solution was adjusted to 2–3 using hydrochloric acid. The resulting OTAB solution was then slowly added to the montmorillonite suspension, and the reaction was carried out at 60–90 °C for 2–5 h. During this process, OTAB dissociates into long-chain alkyl cations in the aqueous medium, which then exchange with the sodium-based montmorillonite layer using Na+. + A displacement reaction occurs, introducing organic cations into the interlayer space of montmorillonite. The originally hydrophilic surface of the montmorillonite sheets is covered with long-chain alkyl groups, changing from hydrophilic to hydrophobic, while simultaneously increasing the interlayer spacing. After the reaction, the reaction solution is filtered, and washed with deionized water until the filtrate is neutral. The resulting product is designated as OTAB-MMT, and dried at 60–100 °C for 8–24 h. It is then added to an aqueous ethanol solution at a mass-to-volume ratio of 1:100 (g / mL), where the volume ratio of ethanol to water is (1–4):(1–4). After ultrasonic dispersion for 10–30 min, a stable OTAB-MMT dispersion is formed.
[0030] Step 2, Preparation of aramid fiber slurry Weigh out aramid filament short-cut fibers and aramid filament precipitated fibers at a mass ratio of (3-7):(3-7). Add both types of fibers to deionized water and stir at 300-800 r / min for 10-20 min to fully disperse the fibers and form a uniform and stable fiber slurry, wherein the concentration of aramid filament (including chopped fibers and precipitated fibers) is 0.1-1.0 wt%.
[0031] Step 3, Preparation of composite slurry The OTAB-MMT dispersion obtained in step 1 is added to the slurry, making the OTAB-MMT content 6-12 wt% of the total mass of the aramid fibers. Stirring is continued at 300-800 r / min for 5-10 min to ensure that the OTAB-MMT is uniformly dispersed among the aramid fibers, thus obtaining the composite slurry.
[0032] Step 4, wet papermaking The composite pulp obtained in step 3 is used to form paper sheets using a wet papermaking process. After vacuum filtration and dehydration, it is dried at 80–120 °C to obtain a preliminary composite insulating paper with a basis weight controlled at 60–120 g / m².
[0033] Step 5, hot pressing treatment The composite insulating paper obtained in step 4 is placed in a hot press and hot-pressed for 5 to 20 minutes at 220–300 °C and 8–15 MPa to obtain organically modified montmorillonite-reinforced aramid insulating paper.
[0034] Example 1: This embodiment provides an organically modified montmorillonite-reinforced aramid fiber insulating paper, the preparation method of which includes the following steps: Step 1) Weigh 10 g of sodium-based montmorillonite and add it to 200 mL of deionized water. Stir at 400 r / min for 3 h at 80 ℃. Separately, dissolve 6.34 g of OTAB in 200 mL of deionized water and adjust the pH to 3 with hydrochloric acid. Add the OTAB solution to the montmorillonite suspension and react at 80 ℃ for 3 h. After filtration and washing until neutral, dry at 80 ℃ for 12 h to obtain OTAB-modified montmorillonite (OTAB-MMT). Add it to an ethanol-water mixture (volume ratio 1:1) at a mass-to-volume ratio of 1:100 (g / mL) and disperse ultrasonically for 20 min to form a stable dispersion.
[0035] Step 2) Prepare the fiber slurry at a mass ratio of 4:6. Weigh 1.01 g of aramid filament short-cut fiber and 1.51 g of aramid filament precipitated fiber, and add deionized water to make the slurry concentration 0.3 wt%. Mechanically stir at 400 r / min for 10 min to fully disperse the fibers and form a uniform and stable slurry.
[0036] Step 3) Add OTAB-MMT at 8 wt% of the total mass of aramid fiber, that is, take 20 mL of OTAB-MMT dispersion and add it to the fiber slurry prepared in step (2), and stir at 400 r / min for 5 min to make it evenly dispersed in the fiber slurry.
[0037] Step 4) The paper sheet is prepared by wet papermaking process. After vacuum filtration and dehydration by pressing, it is dried at 105 °C to obtain a circular paper sheet with a diameter of 20 cm, a mass of 2.51 g, and a basis weight of 80 (±2) g / m².
[0038] Step 5) Place the paper sheet under hot pressing at 250℃ and 12 MPa for 10 min to obtain 8% OTAB-MMT / PSA insulating paper. The actual product is shown below. Figure 2a As shown, the paper surface is flat and the structure is intact. After bending and folding, it is as follows: Figure 2b and Figure 2c As shown, it therefore has good flexibility and formability.
[0039] Example 2: This embodiment is basically the same as Embodiment 1, except that: Step 2) Prepare the fiber slurry at a mass ratio of 4:6. Weigh 1.26 g of aramid filament short-cut fiber and 1.88 g of aramid filament precipitated fiber, and add deionized water to make the slurry concentration 0.3 wt%. Mechanically stir at 400 r / min for 12 min to fully disperse the fibers and form a uniform and stable slurry.
[0040] Step 3) Add OTAB-MMT at 10 wt% of the total mass of aramid fiber, that is, take 31.4 mL of OTAB-MMT dispersion and add it to the fiber slurry prepared in step (2), and stir at 400 r / min for 7 min to make it evenly dispersed in the fiber slurry.
[0041] Step 4) The paper sheet is prepared by wet papermaking process. After vacuum filtration and pressing dehydration, it is dried at 105 ℃ to obtain a circular paper sheet with a diameter of 20 cm, a mass of 3.14 g, and a basis weight of 100 (±2) g / m².
[0042] Step 5) Place the paper sheet under hot pressing at 250 ℃ and 15 MPa for 10 min to obtain 10% OTAB-MMT / PSA insulating paper.
[0043] Example 3: This embodiment is basically the same as Embodiment 1, except that: Step 2) Prepare the fiber slurry at a mass ratio of 4:6. Weigh 0.75 g of aramid filament short-cut fiber and 1.13 g of aramid filament precipitated fiber, and add deionized water to make the slurry concentration 0.3 wt%. Mechanically stir at 400 r / min for 10 min to fully disperse the fibers and form a uniform and stable slurry.
[0044] Step 3) Add OTAB-MMT at 6 wt% of the total mass of aramid fiber, that is, take 11.3 mL of OTAB-MMT dispersion and add it to the fiber slurry prepared in step (2), and stir at 400 r / min for 5 min to make it evenly dispersed in the fiber slurry.
[0045] Step 4) The paper is prepared by wet papermaking process. After vacuum filtration and pressing dehydration, it is dried at 105 °C to obtain a circular paper sheet with a diameter of 20 cm, a mass of 1.88 g, and a basis weight of 60 (±2) g / m².
[0046] Step 5) Place the paper sheet under hot pressing at 250 ℃ and 12 MPa for 8 min to obtain 6% OTAB-MMT / PSA insulating paper.
[0047] Figure 3 The figures show a comparison of the SEM morphology and water contact angle of Na-MMT (a) and OTAB-MMT (b) obtained in Example 1. As can be seen from the figures, the unmodified Na-MMT sheets exhibit a densely stacked sheet morphology with tight bonding between the sheets. However, after OTAB modification, the degree of montmorillonite sheet exfoliation increases, the sheet structure becomes significantly looser, the layered stacking degree decreases, and sheet exfoliation and dispersion can be observed in some areas, with the surface shifting from hydrophilic to hydrophobic.
[0048] Depend on Figure 4a The XRD pattern shows that the (001) diffraction peak of Na-MMT is located at 2θ = 7.02°, corresponding to an interlayer spacing of 1.21 nm. After modification with OTAB, this diffraction peak shifts to 2θ = 4.08°, and the interlayer spacing increases to 2.10 nm. Figure 4b The FTIR spectrum shows that OTAB-MMT exhibits absorption peaks corresponding to the characteristic functional groups of OTAB, indicating that OTAB has successfully intercalated into the montmorillonite interlayer.
[0049] Figure 5The effects of different Na-MMT and OTAB-MMT addition amounts on the AC breakdown strength of aramid fiber insulating paper were investigated. Results showed that when the added OTAB-MMT exceeded 4 wt% of the total aramid fiber mass, the addition of appropriate amounts of montmorillonite (6–12 wt%) improved the breakdown strength of the aramid fiber insulating paper, with OTAB-MMT showing a significantly better reinforcing effect than Na-MMT. When the OTAB-MMT addition amount was 8 wt%, the AC breakdown strength of the composite insulating paper reached its maximum value of 22.47 kV / mm. Further increasing the addition amount led to a slight decrease in insulation performance due to localized filler accumulation, but the overall performance remained superior to the unmodified montmorillonite system, indicating that organic modification can effectively improve the reinforcing efficiency of montmorillonite in paper-based systems.
[0050] Figure 6 The figures show the pore size distribution curves for PSA paper (obtained by directly processing the pulp from step 2 through steps 4) and 5), 8% Na-MMT / PSA paper, and 8% OTAB-MMT / PSA paper. As can be seen from the figures, at the same addition amount, the addition of Na-MMT results in more large pores due to internal filler agglomeration, while the pore size distribution of OTAB-MMT is significantly reduced.
[0051] Depend on Figure 7 As can be seen, 0% represents the result without step 1), while 2%, 4%, and 6% are proportionally reduced according to step 3) of Example 1. The 8% OTAB-MMT / PSA paper has the lowest saturated moisture absorption rate, approximately 9.8%, which is about 58.3% lower than that of PSA paper. This indicates that organically modified montmorillonite can effectively improve the pore structure of the paper and reduce its moisture adsorption capacity, thereby improving the service stability of the insulating paper in high humidity environments.
Claims
1. A method for preparing an organically modified montmorillonite-reinforced arylsulfone insulating paper, characterized in that, Includes the following steps: S1, the sodium montmorillonite dispersion modified with octadecyltrimethylammonium bromide is mixed evenly with aramid slurry, wherein the mass of the sodium montmorillonite modified with octadecyltrimethylammonium bromide is 6-12% of the aramid slurry, to obtain a composite slurry; S2, the composite pulp is formed into paper sheets using a wet papermaking process, and then filtered, dehydrated and dried in sequence to obtain the preliminary composite insulating paper; S3, the pre-formed composite insulating paper is hot-pressed at 220-300 ℃ to obtain organically modified montmorillonite-reinforced aramid insulating paper.
2. The method for preparing organically modified montmorillonite-reinforced arylsulfone insulating paper according to claim 1, characterized in that, The sodium-based montmorillonite dispersion described in S1 is obtained through the following process: The aqueous suspension of sodium montmorillonite was reacted with an aqueous solution of octadecyltrimethylammonium bromide at 60–90 °C for 2–5 h. The amount of octadecyltrimethylammonium bromide added was 1–1.5 times the cation exchange capacity of sodium montmorillonite. The product was then filtered, washed, dried, and dispersed in an aqueous ethanol solution at a ratio of 1 g: 100 mL to obtain the sodium montmorillonite dispersion.
3. The method for preparing organically modified montmorillonite-reinforced arylsulfone insulating paper according to claim 2, characterized in that, In the aqueous suspension of sodium montmorillonite, the ratio of sodium montmorillonite to deionized water is 1 g:(10-30) mL, and the volume of the aqueous suspension of sodium montmorillonite is the same as that of the aqueous solution of octadecyltrimethylammonium bromide. In the ethanol-water solution, the volume ratio of ethanol to deionized water is (1-4): (1-4).
4. The method for preparing organically modified montmorillonite-reinforced arylsulfone insulating paper according to claim 3, characterized in that, The pH value of the aqueous solution of octadecyltrimethylammonium bromide is 2 to 3.
5. The method for preparing organically modified montmorillonite-reinforced arylsulfone insulating paper according to claim 1, characterized in that, The aramid slurry described in S1 is obtained through the following process: Aryl sulfone short-cut fibers and precipitated aramid fibers were added to deionized water at a mass ratio of (3-7):(3-7) and dispersed evenly to obtain aramid slurry.
6. The method for preparing organically modified montmorillonite-reinforced arylsulfone insulating paper according to claim 5, characterized in that, In the aramid slurry, the total mass of aramid chopped fibers and aramid precipitated fibers is 0.1% to 1% of the mass of the aramid slurry.
7. The method for preparing organically modified montmorillonite-reinforced arylsulfone insulating paper according to claim 1, characterized in that, S1. An octadecyltrimethylammonium bromide-modified sodium montmorillonite dispersion and aramid slurry are stirred at 300–800 r / min for 5–10 min to obtain a composite slurry.
8. The method for preparing organically modified montmorillonite-reinforced arylsulfone insulating paper according to claim 1, characterized in that, The drying described in S2 is carried out at 80–120 °C, resulting in a pre-formed composite insulating paper with a basis weight of 60–120 g / m².
9. The method for preparing organically modified montmorillonite-reinforced arylsulfone insulating paper according to claim 1, characterized in that, The composite insulating paper initially formed as described in S3 is hot-pressed at 220–300 °C and 8–15 MPa for 5–20 min.
10. An organically modified montmorillonite-reinforced aramid insulating paper obtained by the preparation method of the organically modified montmorillonite-reinforced aramid insulating paper according to any one of claims 1 to 9.